2015
DOI: 10.2337/db14-1575
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of Protein Tyrosine Phosphatases Enhances Interferon Signaling in Pancreatic Islets

Abstract: Type 1 diabetes (T1D) is the result of an autoimmune assault against the insulin-producing pancreatic b-cells, where chronic local inflammation (insulitis) leads to b-cell destruction. T cells and macrophages infiltrate into islets early in T1D pathogenesis. These immune cells secrete cytokines that lead to the production of reactive oxygen species (ROS) and T-cell invasion and activation. Cytokine-signaling pathways are very tightly regulated by protein tyrosine phosphatases (PTPs) to prevent excessive activa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 30 publications
0
27
0
Order By: Relevance
“…The progressive loss of pancreatic β-cells leads to D1M, which is closely associated with autoimmune assault ( 110 ). During the inflammatory progressive stage, overexpression of JAK-STAT molecules in pancreatic islets has been reported to contribute to β-cell dysfunction ( 111 ). A recent study documented that BRD0476, a novel inhibitor of β-cell apoptosis, impeded inteferon-γ-induced JAK2 and STAT1 signaling to facilitate β-cell survival ( 112 ).…”
Section: Jak-stat Signaling Pathwaysmentioning
confidence: 99%
“…The progressive loss of pancreatic β-cells leads to D1M, which is closely associated with autoimmune assault ( 110 ). During the inflammatory progressive stage, overexpression of JAK-STAT molecules in pancreatic islets has been reported to contribute to β-cell dysfunction ( 111 ). A recent study documented that BRD0476, a novel inhibitor of β-cell apoptosis, impeded inteferon-γ-induced JAK2 and STAT1 signaling to facilitate β-cell survival ( 112 ).…”
Section: Jak-stat Signaling Pathwaysmentioning
confidence: 99%
“…Moreover, free radical-mediated inactivation of phosphatase and tensin homolog (PTEN), which dephosphorylates PIP3, extends the activation of PKB/Akt and its downstream effects (Lee et al, 2012a;Mehdi et al, 2007;Tan et al, 2015). Similarly, free radicals can also inactivate protein tyrosine phosphatases (PTP) by oxidizing catalytic cysteine residues, thereby enhancing receptor-and nonreceptor tyrosine kinase-dependent signaling (Ostman et al, 2011;Stanley et al, 2015).…”
Section: Protective Mechanisms Against Oxidative Stressoxidative Condmentioning
confidence: 99%
“…PTPN2 was the first example of PTP inactivation sensitizing β-cells to death through hyperactivation of IFN-γ-induced STAT1-dependent BIM induction (Moore et al 2009, Santin et al 2011. In addition, we showed that chronic oxidative stress developed during insulitis in the NOD mouse inactivated PTPN2 and PTPN6 and enhanced IFN-γ-dependent STAT1 signalling, culminating in islet death by BIM induction (Stanley et al 2015). These previous studies showed a link for in vivo PTP inactivation enhancing the sensitivity of β-cells to cytokine-induced destruction.…”
Section: Discussionmentioning
confidence: 77%
“…We have previously shown that PTPN6 and PTPN1 are expressed in the pancreas of diabetic NOD mice, and global PTP inactivation enhanced cytokine-induced islet death (Stanley et al 2015). In the present study, we aimed to clarify their specific roles in cytokine signalling regulation in β-cells.…”
Section: Ptpn6 and Ptpn1 Are Expressed In Human And Nod Mouse Isletsmentioning
confidence: 92%
See 1 more Smart Citation